Early Fetal Growth Restriction of Both Twins in a Transgender Man - Alicia Martínez-Varea; Clara Martínez-Sáez; María Patrocinio Tarrazó-Millet; Vicente Diago-Almela (Case Reports in Obstetrics and Gynecology)
Gender dysphoria affects 0.5% of people worldwide. Transgender men display a divergence between the female genetic sex and the gender male identity. To the best of our knowledge, we describe the first case report with regard to a transgender man with a dichorionic diamniotic twin pregnancy obtained by artificial insemination using donor sperm as a monoparental family, presenting early fetal growth restriction of both twins. The patient is a 35-year-old transgender man who had previously received gender-affirming hormone therapy based on testosterone for five years and had a prior bilateral mastectomy as gender-affirming surgery. Whether assisted reproductive techniques have any influence on obstetrical outcomes among these patients and whether prior long-term intake of gender-affirming hormone therapy has an impact on pregnancy and obstetrical outcomes remain to be elucidated.